Nanotechnology in oncology: advances in biosynthesis, drug delivery, and theranostics - Mohamed M. Ammar; Rania Ali; Naira Ali Abd Elaziz; Heba Habib; Fatima M. Abbas; Mohamed Taha Yassin; Khalid Maniah; Rewan Abdelaziz (Discover Oncology)
Abstract Nanotechnology has revolutionized oncology by offering innovative solutions to overcome the limitations of conventional cancer therapies. This review explores the transformative potential of nanotechnology in cancer diagnosis, treatment, and drug delivery, emphasizing the development of sustainable nanocomposites derived from natural sources such as plants and microbes. These eco-friendly nanocomposites enhance therapeutic efficacy, minimize environmental impact, and align with green chemistry principles. Nanoparticles (NPs) enable targeted drug delivery through mechanisms like the enhanced permeability and retention (EPR) effect and active targeting, reducing systemic toxicity and improving treatment outcomes. They also facilitate gene therapy, photothermal and photodynamic therapies, and immune modulation, including the development of cancer vaccines and theranostic platforms. Despite their promise, challenges such as nanoparticle toxicity, immune clearance, and long-term biocompatibility persist. Advances in biodegradable and stimuli-responsive NPs aim to address these issues, ensuring safer and more effective applications. The integration of nanotechnology with personalized medicine and combination therapies holds significant potential for improving cancer treatment efficacy and patient outcomes. However, further research is needed to optimize nanoparticle design, enhance tumor targeting, and ensure clinical translation. This review highlights the critical role of nanotechnology in advancing cancer therapy, underscoring its potential to redefine treatment paradigms while addressing current limitations and future prospects.